The two-faced role of RNA methyltransferase METTL3 on cellular response to cisplatin in head and neck squamous cell carcinoma in vitro model - Ostrowska, Kamila; Rawłuszko-Wieczorek, Agnieszka A.; Ostapowicz, Julia; Suchorska, Wiktoria M.; Golusiński, Wojciech (Frontiers in Oncology, 2024)
Background RNA methyltransferase-like 3 (METTL3) is responsible for methyl group transfer in the progression of m 6 A modification. This epigenetic feature contributes to the structural and functional regulation of RNA and consequently may promote tumorigenesis, tumor progression and cellular response to anticancer treatment (chemo-, radio-, and immunotherapy). In head and neck squamous cell carcinoma (HNSCC), the commonly used chemotherapy is cisplatin, unfortunately cisplatin resistance is still a major cause of tumor relapse and patients' death. Thus, this study aimed to investigate the role of METTL3 on cellular cisplatin response to cisplatin in HNSCC in vitro models.Materials&Methods HNSCC cell lines (H103, FaDu, Detroit-562) with stable METTL3 knockdown (sgMETTL3) knock-ou (KO) established with CRISPR-Cas9 system, were treated with 0.5TPL and 1TPL of cisplatin. Further, cell cycle distribution, apoptosis, CD44/CD133 surface markers expression, and cell's ability to colony formation were analysed in comparison to controls (cells transduced with control sgRNA).The analyses of cell cycle distribution and apoptosis indicated, a significantly higher percentage of cells with METTL3 knockdown KO 1) arrested in G2/S phase, and 2) characterized as a late apoptotic or death in comparison to control. The colony formation assay showed intensified inhibition of a single cell ability to grow into a colony in FaDu and Detroit-562 METTL3-deficient KO cells, while higher colony number was observed in H103 METTL3 knockdown cellsKO cell lines after cisplatin treatment. Also, METTL3-deficiency KO significantly increased cancer stem cells markers' surface expression in all studied cell lines.Our findings highlight the significant influence of METTL3 on the cellular response to cisplatin, suggesting its potential as a promising therapeutic target for addressing cisplatin resistance in certain cases of HNSCC.